Role of Wnt/GSK3beta/beta-catenin signaling pathway in cardiac and pulmonary vascular remodeling - Sklepkiewicz, Piotr Lukasz; Justus Liebig University Giessen (My University, 2010)
Pulmonary Arterial Hypertension is a complex disease associated with a poor prognosis. Many therapeutical strategies have been introduced to PAH patients. All approved therapies targeting vasodilation are effective by improving hemodynamics, exercise capacity and give small improvements in survival in PAH patients (78), however, they failed to reverse the disease. Therefore the focus of the treatment in recent years has changed from vasodilators to anti-proliferative agents and new signaling pathways are needed to be evaluated for future therapies. In our studies we focused on the Wnt signaling pathway, which was recently implicated to many cancerous diseases. In addition it has been shown that this pathway is crucial for cardiovascular diseases. In our study we observed downregulation of well-known canonical Wnt signaling ligands in experimental PAH in rats. GSK3beta and beta-Catenin, which are downstream targets of canonical Wnt signaling, are upregulated in lungs as well as in PASMCs from MCT-induced PAH rats compared to controls on protein level. Further, stimulation of MCT-PASMCs with both PDGF-BB and Wnt3a induced inactivation of GSK3beta, whereas only Wnt3a regulated beta-Catenin accumulation in PASMCs. Constitutive activation of GSK3beta by amino acid substitution S9A (9th serine replaced to alanine) or Y216D (tyrosine replaced to aspartic acid) inhibited serum-induced PASMC proliferation influencing ERK phosphorylation. PDGF-BB-induced proliferation was inhibited by Y216D mutant, which seems to be implicated in PDGF signaling in experimental PAH. The fact that PDGF-induced MCT-PASMC proliferation could be significantly decreased by GSK3beta amino acid residues modulation, collectively indicate the importance of GSK3beta in the pathogenesis of PAH. Significant upregulation of GSK3beta in lung explants of patients with iPAH support a concept that this protein plays a role in development of PAH. Profound changes in pulmonary vasculature in PAH are followed by heart hypertrophy and heart failure. Wnt signaling was previously reported to play crucial role in cardiovascular maintenance and one of our candidate genes was sFRP-1, an extracellular Wnt signaling modulator. We found that sFRP-1 is abundantly expressed in normal mice hearts at 3, 6 and 12 months of age and predominantly localized in cardiomyocytes and endothelial cells suggesting that it may play a significant role in heart function maintenance. To evaluate the role of sFRP-1 in adult hearts we used sFRP-1 KO mice up to 12 months of age. No significant phenotype was observed in these mice up to 6 months of age. At one year of age, sFRP-1 KO mice exhibited significant increase in heart size with age-dependent increase in heart weight to body weight ratio. Additionally to this phenotype, an increase in left ventricular dimensions, posterior wall thickness, and a decrease in fractional shortening occurred in sFRP-1 KO mice at 1 year of age. Increased formation of fibrotic lesions in myocardium of 1-year-old mice collectively suggest that loss of sFRP-1 leads to cardiac hypertrophy and finally cardiomyopathy. Determination of wide mRNA expression profile showed that parts of Wnt signaling in heart of 1-year-old mice are significantly upregulated mainly the Frizzled 2 pathway and pro-hypertrophic, pro-fibrotic Wnt dependent genes like Fgf4, WIF1 and already well described Wisp1. Increased ß-catenin expression and its accumulation in intercalated disks suggested a decrease in Wnt/ß-catenin transcriptional activity that was confirmed by significant down regulation of cyclin D and cMyc. Suppression of canonical Wnt signaling is possible mechanism of downregulation of connexin43 and loss of heart function both described in human idiopathic and dilated cardiomyopathies. In conclusion, we describe that sFRP-1 is a critical factor in maintaining normal cardiovascular function and loss of this gene induces cardiac remodeling which progresses to dilated cardiomyopathy. The mechanism is a supression of Wnt mediated canonical signaling pathway followed by decrease in connexin 43 expression, protein that is very important in heart function and its contraction ability. Yet more studies needs to be done to elucidate and propose final role of Wnt signaling in mainaining cardiovascular system function.

Die pulmonale arterielle Hypertonie (PAH) ist eine Erkrankung der Lungengefäße, die mit einer sehr schlechten Prognose assoziiert ist. Die zur Therapie zugelassenen Medikamente umfassen Endothelin-Rezeptor Antagonisten, Prostanoide und Phosphodiesterase 5 Hemmstoffe, alles gefäßerweiternde Medikamente, die zwar die Belastbarkeit der Patienten erhöhen, aber die Erkrankung nicht heilen können. Daher ist es notwendig, neue Signalwege für zukünftige Therapien zu evaluieren. In unseren Untersuchungen haben wir uns auf den Wnt Signalweg fokussiert, der bei vielen malignen Erkrankungen eine Rolle spielt. Zusätzlich wurde gezeigt, dass dieser Signalweg auch bei anderen kardiovaskulären Erkrankungen involviert ist. In unserer Studie zeigen wir die Abnahme der Liganden des Wnt Signalweges bei experimenteller pulmonaler Hypertonie im Rattenmodell (Monocrotalin (MCT) Injektion). GSK3beta und beta-Catenin, die nachgeschalteten Ziele des Wnt Signalweges, waren auf Protein-Ebene erhöht, sowohl in Lungen als auch in pulmonalarteriellen glatten Muskelzellen (PASMCs) von MCT Ratten im Vergleich zur gesunden Tieren. Die Behandlung von MCT-PASMCs mit dem Wachstumsfaktor PDGF-BB oder mit Wnt3a führte zu einer Inaktivierung von GSK3beta, wobei nur Wnt3a die beta-Catenin Akkumulation in PASMCs regulierte. Um die Rolle von GSK3beta näher zu untersuchen, generierten wir konstitutiv aktive Mutanten bei denen die Aminosäure S9A (9tes Serin mit Alanin ersetzt) oder Y216D (Tyrosin mit der Aminosäure Aspartat ersetzt) ersetzt wurden. Eine Überexpression dieser GSK3 Mutanten in PASMCs inhibierte die Serum-induzierte Proliferation wobei die extrazellulär regulierte Kinase (ERK) als nachgeschalteter Signalweg identifiziert wurde. Untersuchungen an humanem Lungengewebe von Patienten mit PAH zeigten eine signifikante Erhöhung von GSK3beta und unterstützen die Theorie, dass dieses Protein eine Rolle in der Entwicklung der PAH spielt. Profunde Veränderungen der pulmonalen Gefäßstruktur bei PAH führen zu Herzhypertrophie und Herzversagen. Es wurde bereits erwähnt, dass der Wnt Signalweg eine entscheidende Rolle bei der Aufrechterhaltung der kardiovaskulären Funktion spielt, und eines unserer untersuchten Gene war sFRP-1, ein extrazellulärer Modulator des Wnt Signalweges. Wir konnten zeigen, dass sFRP-1 in normalen Mausherzen im Alter von 3, 6 und 12 Monaten exprimiert wird und v.a. in Kardiomyozyten und Endothelzellen lokalisiert ist, so dass man vermuten kann, dass es eine signifikante Rolle in der Aufrechterhaltung der Herzfunktion spielt. Um die Rolle von sFRP-1 in erwachsenen Herzen zu untersuchen, wurden sFRP-1 KO Mäuse im Alter von bis zu 12 Monaten untersucht. Dabei konnte kein signifikanter Unterschied im Phänotyp bei den Mäusen im Alter von bis zu 6 Monaten beobachtet werden. Im Alter von einem Jahr zeigten sFRP-1 KO Mäuse eine Zunahme der Herzgröße mit einer altersabhängigen Zunahme des Verhältnisses von Herzgewicht zu Körpergewicht. Darüberhinaus trat bei den sFRP-1 KO Mäusen im Alter von einem Jahr eine Zunahme der linksventrikulären Herzdimensionen, der hinteren Herzwanddicke und eine Abnahme des Fractional Shortening (FS) auf. Die vermehrte Entstehung von fibrotischen Läsionen im Myokard von ein Jahr alten Mäusen lässt vermuten, dass ein Verlust von sFRP-1 zu kardialer Hypertrophie führt, die eine dilatierte Kardiomyopathie zur Folge hat. Die Bestimmung eines weitläufigen mRNA Expressionsprofils hat gezeigt, dass Teile des Wnt Signalweges im Herzen signifikant erhöht sind, dabei v.a. der Frizzled 2 Signalweg und prohypertrophische, profibrotische und Wnt abhängige Gene wie Fgf4, WIF1 und das bereits gut beschriebene Wisp1. Die erhöhte beta-Catenin-Expression läßt eine Abnahme der transkriptionellen Aktivität von Wnt/beta-Catenin vermuten. Die Suppression des bewährten Wnt Signalweges ist ein möglicher Mechanismus zur Senkung von Connexin 43 und zum Verlust der Herzfunktion, die beide in menschlischer idiopathischer und dilatativer Kardiomyopathie beschrieben werden. Abschließend beschreiben wir, dass sFRP-1 ein kritischer Faktor in der Aufrechterhaltung der kardiovaskulaeren Funktion ist und ein Verlust dieses Gens ein kardiales Remodelling induziert, das zu dilatativer Kardiomyopathie führt. Der Mechanismus besteht aus der Suppression des Wnt vermittelten, bewährten Signalweges, gefolgt von einer Abnahme der Connexin 43 Expression, eines Proteins, das sehr wichtig fuer die Herzfunktion und ihre Kontraktionsfähigkeit ist. Es müssen noch mehr Studien erfolgen, um die endgültige Rolle des Wnt Signalweges in der Aufrechterhaltung der Funktion des kardiovaskulären Systems aufzuklären.
Die Rolle des WNT/GSK3-beta/beta-Catenin-Signalwegs für das kardiale und pulmonale Gefäß-Remodelin
Keywords: ddc:610